DIGITALISASI PENGELOLAAN SURAT PADA PT PUPUK SRIWIDJAJA MENGGUNAKAN METODE FAST - Nurul Adha Oktarini Saputri; R.M. Nasrul Halim (Jurnal Teknologi Informasi Mura (JTI), 2026)
Mail management is an important part of the company's administrative process, especially in terms of archiving, recording, and efficient distribution of documents. PT Pupuk Sriwidjaja Palembang as a large company requires a system that is able to handle letter management effectively and in a structured manner. So far, the letter management process is still mostly done manually, potentially causing problems such as delays, lost documents, and difficulties in searching for archives. This study aims to design and develop a web-based letter management system to support the digitalization process of administration at PT. Pupuk Sriwidjaja Palembang. The system built is a web-based application and uses the FAST (Framework for the Application of Systems Thinking) method, which is a structured approach in information system development. This study implements all FAST stages from needs analysis to system testing and evaluates the level of user acceptance using the System Usability Scale (SUS) method. The result of this study is a digital letter management application that supports the process of incoming and outgoing letters, recording, and searching for archives quickly and in a structured manner. The results of the system evaluation using the SUS method obtained a score of 84.0 which is in the Excellent category with an Acceptable user acceptance level. The implementation of the system is able to accelerate the document search process, improve the letter archiving process, and reduce the use of physical documents in the administrative process so that it can support the digitalization of administration at PT Pupuk Sriwidjaja Palembang.